Controlled ovarian hyperstimulation with sequential letrozole co-treatment in normo/high responders. (3rd March 2016) - Ecemis, Tolga; Tasci, Yasemin; Caglar, Gamze Sinem
Abstract: Objective : To investigate the effect of co-administration of letrozole in an ovarian stimulation protocol using recombinant FSH and GnRH antagonists for ICSI in normo/high responders. Methods : Computerized data of 320 antagonist ICSI/ET cycles with or without letrozole were retrospectively analyzed. In 105 cases, letrozole (5 mg/day) was started at the second day of the cycle continued for 5 days. At the second day of letrozole, gonadotropins were added. The remaining 215 cases were stimulated with recombinant FSH only. In all cases on day 6, GnRH antagonist was started. Ovarian stimulation protocols with or without letrozole were compared for cycle outcome parameters. Results : In cycles with letrozole, significantly lower gonadotropin consumption and lower peak estradiol levels were found. In cycles with letrozole, mean number of metaphase II and fertilized oocytes retrieved were significantly higher compared to cycles without letrozole. The pregnancy and clinical pregnancy rates were similar. Conclusion : Should the number of oocytes retrieved being higher in letrozole group might indicate that letrozole might contribute to successful ovarian stimulation with a lower dosage of gonadotropins. Despite the lower peak estradiol levels, pregnancy rates being similar to other group also support the idea that letrozole can contribute to normal potential of implantation.